THE ENHANCEMENT OF TEMPERATURE IN BOILER BY STEAM INJECTION - Septiana, Iriani Reka; Daniar, Rima; Puspa, Dilia; Kholidah , Nurul (AUSTENIT, 2023)
The boiler is equipment widely used in various industrial sectors such as power plants, fertilizer plants, paper mills, and others. The combustion chamber is an important part of the boiler which can determine the quality of the steam product. The main problem has happened in combustion chambers such as unburned hydrocarbon/carbon loss which is called fouling. Fouling has occurred in many boilers, which use coal or oil as fuel for the production of steam and decreases boiler performance. The purpose of this research is to increase temperature by adding steam injection to reduce fouling to compare with and without steam injection. Two indicators that have the potential to enhance heat transfer are the elevation in temperature and the reduction in fouling percentage. The variables in this research were air flow of 15 L/min, 17,5 L/min, and 20 L/min and steam injection pressure of 2 bars, 3 bars, and 4 bars. The maximum temperature enhancement was 37,5% in 15 L/min of air flow at a steam injection pressure of 2 bars and 3 bars. The maximum fouling abatement was 78,57% in 15 L/min at a steam injection pressure of 4 bars.